Clinical trial enrollment of adolescents and young adults with sarcoma. Issue 18 (11th May 2017) - Davis, Lara E.; Janeway, Katherine A.; Weiss, Aaron R.; Chen, Yen‐Lin E.; Scharschmidt, Thomas J.; Krailo, Mark; Glade Bender, Julia L.; Kopp, Lisa M.; Patel, Shreyaskumar R.; Schwartz, Gary K.; Horvath, L. Elise; Hawkins, Douglas S.; et al.
Abstract : More than half of all sarcomas occur in adolescents and young adults (AYAs) aged 15 to 39 years. After the publication of the AYA series in the April 1, 2016 issue of Cancer, several leaders in the field of sarcoma across disciplines gathered to discuss the status of sarcoma clinical research in AYAs. They determined that a focused effort to include the underrepresented and understudied AYA population in current and future sarcoma clinical trials is overdue. Trial enrichment for AYA‐aged sarcoma patients will produce more meaningful results that better represent the disease's biology, epidemiology, and treatment environment. To address the current deficit, this commentary outlines changes believed to be necessary to expediently achieve an increase in the enrollment of AYAs in sarcoma clinical trials. Cancer 2017;123:3434‐40 . © 2017 American Cancer Society . Abstract : A focused effort to include the underrepresented and understudied adolescent and young adult population in current and future sarcoma clinical trials is overdue. Increased enrollment of adolescents and young adults in sarcoma trials across cooperative groups will produce more meaningful results that better represent the disease's biology, epidemiology, and treatment environment.